2015
DOI: 10.1111/1460-6984.12149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of presentations on listener transcriptions and reliability in the assessment of speech intelligibility in children

Abstract: Information about the number of times an utterance is presented to the listener is important and should therefore always be included in reports of research involving intelligibility assessment. There is a need for further research and discussion on listener abilities and strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Lagerberg et al . (2015) found that intelligibility scores of children with speech difficulties, as measured by orthographic transcription, increased as the number of presentations of the sentence stimuli increased from one to three times. However, the frequency of listeners hearing the sentences once versus twice was not recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lagerberg et al . (2015) found that intelligibility scores of children with speech difficulties, as measured by orthographic transcription, increased as the number of presentations of the sentence stimuli increased from one to three times. However, the frequency of listeners hearing the sentences once versus twice was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The listeners did not know the target. Based on Lagerberg et al (2015), the listeners were allowed to listen to each sentence twice before moving on to the next item. Other previous studies that recruited listeners to judge speech intelligibility also allowed two repetitions of speech stimuli (e.g., Yorkston and Beukelman 1981).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to repeated sentences, we found that 17% of the material in this study was listened to at least twice despite instructions that discouraged repeated listening. Since speech intelligibility score has been shown to increase with the number of repetitions (Lagerberg et al, 2015), there is a possibility that speech intelligibility was overestimated in some cases. However, and importantly, there were no indications that these extra repetitions had any systematic effect on the results, on the whole, seeing that the proportion of repeated sentences were comparable across stimulation conditions.…”
Section: Critique Of the Methodsmentioning
confidence: 99%
“…The most common measurement for assessing intelligibility is to transcribe speech samples orthographically. The reliability of the transcription of spontaneous speech improves with the number of times the transcribers listen to the utterances (Lagerberg et al, 2015).…”
Section: Intelligibilitymentioning
confidence: 99%